The impact of relationship‐contingent self‐esteem on mate retention and reactions to threat. Issue 4 (10th December 2018) - Holden, Christopher J.; Zeigler‐Hill, Virgil; Shackelford, Todd K.; Welling, Lisa L. M.
Abstract : Relationship‐contingent self‐esteem (RCSE) refers to when feelings of self‐worth are derived from romantic relationships. RCSE influences views of the self and the functioning of romantic relationships. The relationship between RCSE and mate retention behaviors was examined across three studies. Study 1 examined whether self‐esteem level and RCSE predicted mate retention behaviors. Studies 2 and 3 examined whether self‐esteem level and RCSE predicted mate retention behaviors following manipulations of threat to the relationship. Individuals with high RCSE were more likely to engage in benefit‐provisioning mate retention behaviors, particularly following certain threats. RCSE was also associated with cost‐inflicting mate retention behaviors, but these associations were inconsistent.